THE ROLE OF ETHICS AND BUSINESS REPUTATION FORMED BY HUMAN POTENTIAL IN ACHIEVING COMPETITIVENESS OF THE ENTERPRISE - CAMARA, Balla Moussa; ZAMLYNSKYI, Viktor (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the importance of ethics and business reputation in the context of achieving the global goals of sustainable development. The influence of ethical principles of personnel management and corporate social responsibility on key aspects of the company's activity, such as competitiveness, financial stability and long-term partnership relations, is analyzed. The importance of compliance with ethical norms is emphasized as a basis for the formation of the company's reputational capital, which becomes an integral component of success in modern markets. Business reputation is considered not only as an intangible asset, but also as a strategic resource that affects building a strong team within the enterprise, attracting investment, retaining customers and increasing employee loyalty.Particular attention is paid to the environmental, social and economic aspects of sustainable development, where the ethical behavior of companies becomes a key factor for achieving long-term results. Statistical data and real examples from the practice of international companies that implement innovative approaches in ethics and reputation management are presented, demonstrating their positive impact on financial results and competitive positions. The conclusions of the article are based on practical cases and confirm that the integration of ethical principles into the company's development strategy is an effective tool for achieving the goals of sustainable development. The human potential of the enterprise seeks to create a positive image, makes the staff more loyal and motivated, and as a result strengthens the team, reduces the rotation and turnover of personnel, which must be carried out according to moral and ethical standards and social responsibility. The company's ability to adhere to high ethical standards in interaction with customers, partners and society becomes a key condition for its successful integration into global markets, which are becoming more and more focused on social and environmental aspects of business activities based on circularity and sustainable development.
Keywords: competitiveness; ethics; business reputation; human potential; sustainable development; corporate social responsibility; reputation capital; team building; circularity